PENERAPAN MEDIA LINGKUNGAN SEKITAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERPEN KELAS V DI MI THORIQUL HUDA KOTA BATU - Nur Nikmatul Amalia; Ika Ratih Sulistiani; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstrakIn this era Indonesian language subjects especially the writing component is poorly handled since students in elementary school. In fact writing is not an instant thing but it needs to practice continuously in order to produce a perfect writing. Lack of handling in writing can cause a big problem where writing is used as personal interest. This research was conducted in Grade 5 MI Thoriqul Huda Kota Batu. The method used in this research is the research of class actions using a qualitative approach. In this study conducted 2 cycles, using the media around the environment to improve short story writing skills and achieve increased results in each cycle. The media that arround the environment is effectively used in improving writing skills, because with the this media the students are motivated to pour his ideas into writing form.Keyword: Media,  surrounding environment, writing short stories and learning outcomes